Study of Gastro-Oesophageal Reflux Disease among Patients with Type 2 Diabetes Mellitus presenting to Medicine Department at a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Mahato, Arun Kumar; Shah, Madhu; Shrestha, Nischal (Birat Journal of Health Sciences, 2022)
Introduction: Gastro-oesophageal reflux disease is a chronic condition in which stomach contents regurgitates up into oesophagus causing symptoms like acidic taste in mouth, heart burn, bad breath and chronic cough. There is high prevalence of GERD in patients with Type 2 diabetes mellitus in the western countries, but such related data in our country are just few. Objectives: To find out the prevalence of gastroesophageal reflux among patients with Type 2 Diabetes Mellitus attending Nobel Medical College Teaching Hospital. Methodology: This was a descriptive cross-sectional study carried out in Department of Medicine of a tertiary care hospital from July 2020 to June 2021. Ethical approval was taken from Institutional Review Committee of Nobel Medical College Teaching Hospital (Reference number: 464/2020). Convenience sampling was done and data was collected from 191 patients presenting to the department. Collected data was entered, analysed in Statistical Package for the Social Sciences version 21 and documented for study. Point estimate at 95% Confidence Interval and descriptive statistics were interpreted as frequency, percentage, or as mean and standard deviations. Results: Among 191 patients with type 2 diabetes, gastroesophageal reflux was seen in 78 (40.84%) (33.87-47.81 at 95% Confidence Interval) with more prevalent in male 42 (53.84%) than female 36 (46.15%). Mean duration of type 2 diabetes among reflux cases was 10.20± 5.40 years. Conclusions: Gastroesophageal reflux was common associated condition among Diabetic patients.